Capsular Type, Sequence Type and Microbial Resistance Factors Impact on DNase Activity of Streptococcus agalactiae Strains from Human and Bovine Origin - Florindo, Carlos (2019)
Extracellular deoxyribonucleases (DNases) contribute to the spread of pathogenic bacteria through the evasion from host innate immunity. Our main objective was to evaluate the production of extracellular DNases by human and bovine Streptococcus agalactiae clinical strains and perform a correlation of genetic lineages and DNase activity with capsular type, genetic determinants, clinical origin (colonization and infection), and host (human or bovine). DNase activity was evaluated by qualitative and quantitative assays for a collection of 406 human (n = 285) and bovine (n = 121) strains. All (121/121) bovine were isolated from mastitis and revealed to be DNase (+), indicating a putative pathogenic role in this clinical scenario. From the human S. agalactiae strains, 86% (245/285) showed DNase activity, among which all strains belonging to capsular types, namely, Ia, Ib, III-2, and IV. All CC17 strains (n = 58) and 56/96 (58.3%) of the CC19 displayed DNase activity. DNase (-) strains belonged to the CC19 group. However, the subcharacterization of CC19 S. agalactiae strains through multiple-locus variable number tandem repeat analysis (MLVA), antibiotic resistance, mobile elements, and surface proteins did not provide any distinction among DNase producers and non-producers. The production of DNases by all human CC17 strains, about two-fifths of human CC19, and all bovine strains, suggest an important contribution of DNases to hypervirulence.